Ethics, power, internationalisation and the postcolonial: a Foucauldian discourse analysis of policy documents in two Scottish universities. Issue 1 (2nd January 2018) - Guion Akdağ, Emma; Swanson, Dalene M.
ABSTRACT: This paper provides a critical discussion of internationalisation in Higher Education (HE), and exemplifies a process of uncovering the investments in power and ideology through the partial analysis of four strategic internationalisation documents at two Scottish Higher Education institutions, as part of an ongoing international study into the ethics of internationalisation (EIHE). 1 A Foucauldian discursive analytical approach is employed in analysing the policy documents. It reveals the relationships between power and knowledge in the constitution of regimes of truth within internationalisation, while serving to interrogate the dynamics of the affective and ethical in the comprising of such relationships and imaginaries. A critical postcolonial theorisation works in tandem with a Foucauldian approach in uncovering the relations of power discursively at work and the discursive effects of power in institutional terms. Four key themes are identified within the documents and critically discussed. The discussions serve to demonstrate that a lack of critical engagement with internationalisation discourses in Higher Education has the effect of reifying a dominant view and suppressing the emergence of alternative discourses. A critical postcolonial lens facilitates interpretability of power dynamics through and beyond internationalisation in Higher Education to consider the ethical effects of such power in its investments in global inequality, injustice and oppression within the global modernist imaginary.